Comparison of thermoelectric properties of sorted and unsorted semiconducting single-walled carbon nanotube free-standing sheets. (1st December 2022) - Borah, Angana; Huang, Wenxin; Ishii, Taiki; Yamaguchi, Ryohei; Honjo, Emi; Tanaka, Naoki; Fujigaya, Tsuyohiko
Abstract: Semiconducting single-walled carbon nanotubes (s-SWCNTs) are promising materials for thermoelectric generation (TEG) because of their large theoretical Seebeck coefficient ( S ). In this study, to discuss superiority of s-SWCNTs for TEG devices, thermoelectric properties of free-standing s-SWCNT sheets were compared with unsorted SWCNT sheets. To obtain the highest power density, the films were doped with triethyloxonium hexachloroantimonate and 2-(2-methoxyphenyl)-1, 3-dimethyl-2, 3-dihydro-1 H -benzo[ d ]imidazole as the hole and electron dopants, respectively. The doped s-SWCNT sheets exhibited higher S but lower electrical conductivity than those of the unsorted SWCNT sheets. Consequently, the power factor of the s-SWCNT sheets was lower than that of the unsorted SWCNT sheets.